Estimating Kidney Function in the Critically Ill Patients - Gemma Seller-Pérez; Manuel E. Herrera-Gutiérrez; Javier Maynar-Moliner; José A. Sánchez-Izquierdo-Riera; Anibal Marinho; José Luis do Pico (Critical Care Research and Practice)
Glomerular filtration rate (GFR) is an accepted measure for assessment of kidney function. For the critically ill patient, creatinine clearance is the method of reference for the estimation of the GFR, although this is often not measured but estimated by equations (i.e., Cockroft-Gault or MDRD) not well suited for the critically ill patient. Functional evaluation of the kidney rests in serum creatinine (Crs) that is subjected to multiple external factors, especially relevant overhydration and loss of muscle mass. The laboratory method used introduces variations in Crs, an important fact considering that small increases in Crs have serious repercussion on the prognosis of patients. Efforts directed to stratify the risk of acute kidney injury (AKI) have crystallized in the RIFLE or AKIN systems, based in sequential changes in Crs or urine flow. These systems have provided a common definition of AKI and, due to their sensitivity, have meant a considerable advantage for the clinical practice but, on the other side, have introduced an uncertainty in clinical research because of potentially overestimating AKI incidence. Another significant drawback is the unavoidable period of time needed before a patient is classified, and this is perhaps the problem to be overcome in the near future.